Serum NT-proBNP Levels Are Not Related to Vitamin D Status in Young Patients with Congenital Heart Defects. (3rd February 2016) - Passeri, E.; Rigolini, R.; Costa, E.; Verdelli, C.; Arcidiacono, C.; Carminati, M.; Corbetta, S.
Abstract : Context . Hypovitaminosis D frequently occurs in early life and increases with age. Vitamin D has been suggested to influence cardiac performance and N-terminal-pro-type B natriuretic peptide (NT-proBNP) release in adults with heart failure. Objectives . To assess the vitamin D status and the impact of hypovitaminosis D on circulating NT-proBNP levels in young patients with congenital heart defects (CHD). Design and Patients . This cross-sectional study included the assessment of serum 25-hydroxyvitamin D (25OHD), parathyroid function markers, and NT-proBNP levels in a series of 230 young in-patients (117 females, 113 males; 6.4 (4.0–9.1) years (median, interquartile range)) with CHD. Results . Serum 25OHD levels <20 ng/mL were detected in 55.3% of patients. Optimal 25OHD levels (>30 ng/mL) occurred in 25% of patients. Serum 25OHD levels inversely correlated with age (r = - 0.169, P = 0.013 ) and height standard deviation score (r = - 0.269, P = 0.001 ). After correction for age, 25OHD negatively correlated with serum PTH levels (β = - 0.200, P = 0.002 ). PTH levels above the upper quartile (44 pg/mL) occurred in 32% of hypovitaminosis D patients. Serum NT-proBNP levels were not correlated with 25OHD and PTH levels. Conclusions . Half of the young CHD patients were diagnosed with 25OHD deficiency and a third of hypovitaminosis D patients experienced hyperparathyroidism. Nonetheless, serum NT-proBNP levels were not associated with hypovitaminosis D as well as hyperparathyroidism.